Trauma-Informed Care in Child Welfare: An Imperative for Residential Childcare Workers - Brend, Denise Michelle; Sprang, Ginny (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2020)
Context: Rates of traumatization among residential child welfare professionals are alarmingly high. The well-being of these professionals is associated both with their intention to stay in their jobs and outcomes of children in their care. Several risk factors threaten the well-being of child welfare professionals, including primary and secondary exposure to experiences with the potential to provoke posttraumatic stress reactions. Objectives: This manuscript details experiences empirically shown to have potential negative impacts on professional well-being, discusses why these impacts are of particular concern for residential childcare workers, and describes the types of organizational cultures and climates that appear to mitigate these negative impacts. Implications: Trauma-informed care at the organizational level is proposed both as a means to reduce harm to child-welfare professionals and promote the rehabilitation of children within the child welfare system.